Managers gender bias from the perspective of Chinese student - Lu, Qian Qian (2018)
This study focuses on the quantitative relationship between the manager gender and the employee gender. By reviewing gender discrimination and gender preference, this research explores whether there is a positive relationship in the organization between the gender number of managers and the gender number of employees. This study mainly adopts the qualitative research method to conduct a questionnaire survey among 300 managers and interview with ten managers. After analyzing, it found that managers are more likely to hire female employees when they are female. In other words, as the number of female managers increases, the number of women employed increases. Keywords: gender discrimination, gender preference